2008
DOI: 10.1111/j.1749-4486.2008.01764.x
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of spontaneous healing in traumatic perforations of the tympanic membrane

Abstract: The rate of spontaneous healing of traumatic tympanic membrane perforation varied inversely with age of patient and size of perforation. It was delayed by middle-ear infection, as well as in ears that sustain direct injuries and in ears that had wrong interventions. However, it was not dependent on whether the perforation was in the anterior or posterior location. Logistic regression analysis revealed that penetrating injuries sustained through the ear canal and the ear syringing intervention were the only ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
87
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 14 publications
12
87
1
6
Order By: Relevance
“…A shared histological feature of both structures is their lack of vascular supply implying that in any event of injury the process of healing cannot follow traditional mechanisms of repair (13). Although not specifically tested, it then becomes more natural for fetal membranes to follow the repair sequence of other avascular human tissues such as cornea and tympanic membrane where the key event is the migration of the epithelium adjacent to the site of injury across the defect (14)(15)(16).…”
mentioning
confidence: 99%
“…A shared histological feature of both structures is their lack of vascular supply implying that in any event of injury the process of healing cannot follow traditional mechanisms of repair (13). Although not specifically tested, it then becomes more natural for fetal membranes to follow the repair sequence of other avascular human tissues such as cornea and tympanic membrane where the key event is the migration of the epithelium adjacent to the site of injury across the defect (14)(15)(16).…”
mentioning
confidence: 99%
“…With multivariate analysis, we found that perforation size was the single determining factor related to closure time, a finding also reported in some other studies. 2,4 In addition, some authors have stressed the negative influence of ear discharge and increasing age on closure time. 3,4 We found no obvious importance of perforation location, a finding supported by others.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 In addition, some authors have stressed the negative influence of ear discharge and increasing age on closure time. 3,4 We found no obvious importance of perforation location, a finding supported by others. 4 Previous reports of the importance of inverted and everted edges are contradictory, 3,5 but it has been stated that the type of epithelial migration has importance for closure time but not for closure rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2] The rate of spontaneous healing ranges between 48-94%. [6][7][8][9][10][11] Griffen reported 90% spontaneous healing of TM perforation within 3 months of injury. 12 Kristensen reported 78.7 % spontaneous healing within 2 weeks of injury whereas Chun et al reported 76% of complete spontaneous healing within 3 weeks.…”
Section: Discussionmentioning
confidence: 99%